2018
DOI: 10.21162/pakjas/18.4631
|View full text |Cite
|
Sign up to set email alerts
|

EFFECT OF INTENSIVE AND SEMI-INTENSIVE MANAGEMENT SYSTEMS ON GROWTH PERFORMANCE AND ECONOMICS OF MARECHA (Camelus dromedarius) CALVES REARED UNDER DESERT CONDITIONS

Abstract: Twelve Marecha calves were allotted randomly to two comparable groups of 6, (3♂ and 3♀). First group animals were reared under intensive management system (IMS), fed concentrate @ 1 kg/h/d plus crop residues of gram (Cicer arientinum) adlibitum while in second group, calves were reared under semi-intensive management system (SIMS), sent for grazing 8 hours daily plus gram crop residues ad lib. Twice watering was done in both the groups. At end of trial mean body weight and ADG of male and female calves was sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 7 publications
0
14
0
Order By: Relevance
“…After the 120-day trial period, the overall weight gain and daily weight gain (DWG) (growth rate) were 80.8 ± 2.7, 77.8 ± 2.7 kg and 670, 650 g/days for male and female calves in IMS, respectively, and 64.5 ± 2.6, 52.9 ± 2.6 kg and 540, 440 g/days for male and female calves in EMS, respectively ( Table 3). The daily feed intake (DFI) of crop residues was found to vary significantly (p < 0.05) among calf groups Faraz et al (2017Faraz et al ( , 2018.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…After the 120-day trial period, the overall weight gain and daily weight gain (DWG) (growth rate) were 80.8 ± 2.7, 77.8 ± 2.7 kg and 670, 650 g/days for male and female calves in IMS, respectively, and 64.5 ± 2.6, 52.9 ± 2.6 kg and 540, 440 g/days for male and female calves in EMS, respectively ( Table 3). The daily feed intake (DFI) of crop residues was found to vary significantly (p < 0.05) among calf groups Faraz et al (2017Faraz et al ( , 2018.…”
Section: Resultsmentioning
confidence: 99%
“…ADG was 800 g in the zero browsing group as compared to 350 g in the free browsing group, while in present study, a lower DWG was observed in IMS due to the limited supply of concentrate. Faraz et al (2018), comparing the IMS with the SIMS regarding growth rate of camel calves, found a higher growth rate in male calves under IMS than SIMS. The values of the present study are very close to other study reported in which higher growth rates were achieved in EMS than SIMS (Faraz et al, 2017).…”
Section: Diet Effect On Growthmentioning
confidence: 95%
See 1 more Smart Citation
“…In Kenya under proper nutrition reported average daily weight gain in camel calves was 870 and 570 g from birth to 30 days and from birth to 180 days, respectively (Wilson, 1992) while in Egypt El-Badawi (1996) reported 830-970 g daily weight gain from birth to 180 days in dromedary calves. Faraz et al (2018) comparing intensive management system (IMS) with semi-intensive management system (SIMS) regarding growth rate of camel calves found also higher growth rate in male calves under IMS than SIMS. The values of present study also very close to their other study reported in which higher growth rates was achieved in EMS than SIMS (Faraz et al, 2017).…”
Section: Effect Of Diet On Growthmentioning
confidence: 99%
“…Reported weight gain in calves was 411 g/d in males and 380 g/d in females while weight gain after the sexual maturity was 120 g/d in males and 60 g/d in females in northern Kenya (Musavaya, 2003). Faraz et al (2017Faraz et al ( , 2018Faraz et al ( , 2019b compared the growth performance of camel calves in different management systems and found higher weight gain in male calves than female calves.…”
Section: Effect Of Sex On Growthmentioning
confidence: 99%